2022
DOI: 10.3126/ajms.v13i7.43177
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of babies born to mothers with antepartum eclampsia: A study from tertiary care hospital of Central India

Abstract: Background: Eclampsia is a major cause of perinatal mortality. There is a need for studies that will correlate maternal factors and perinatal outcome, which will provide potential strategies to improve fetal outcomes in pregnancies complicated by eclampsia. Aims and Objectives: This study aims to study perinatal outcome of babies born to mothers with antepartum eclampsia and to correlate outcomes with convulsion delivery interval. Materials and Methods: A study included 200 patients diagnosed and managed as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…11 In order to enhance neonatal and mother outcomes, a tertiary care hospital's study identified eclampsia as a primary cause of perinatal mortality. 12 This emphasizes the significance of early diagnosis, quick intervention, and prompt referral from peripheral health centres.…”
Section: Discussionmentioning
confidence: 99%
“…11 In order to enhance neonatal and mother outcomes, a tertiary care hospital's study identified eclampsia as a primary cause of perinatal mortality. 12 This emphasizes the significance of early diagnosis, quick intervention, and prompt referral from peripheral health centres.…”
Section: Discussionmentioning
confidence: 99%